If You Build It Will They Come? Does Involving Community Groups in Playground Renovations Affect Park Utilization and Physical Activity?. (January 2016) - Slater, Sandy; Pugach, Oksana; Lin, Wanting; Bontu, Anita
In a sample of racially, ethnically, and socioeconomically diverse neighborhoods, using a quasi-experimental, prospective, longitudinal study design, we examined whether involvement of community groups in playground design selection, installation, and ongoing maintenance influences park utilization and moderate-to-vigorous physical activity (MVPA) post-playground renovations ( N = 78 matched parks, 39 intervention/39control). Parks were matched on size, proximity, neighborhood socioeconomic status, and race/ethnicity. In summer/fall 2013 and 2014, baseline and 12-month follow-up data were collected on park utilization and physical activity, presence and condition of park features, incivilities, programming, and safety. Analyses were conducted using Poisson mixed-effects regression models. Significant increases between baseline and 12-month follow-up were found for park utilization and the number of people engaged in MVPA at the .05 significance level. Study results can provide communities with evidence to inform future policy decisions on how to increase park utilization in diverse neighborhoods.